Statistical Analysis of Wind Speed Data Based on Weibull and Rayleigh Distribution - Ivana Pobocikova; Zuzana Sedliackova; Jan Simon (Communications - Scientific letters of the University of Zilina, 2014)
In this paper the wind speed data from Meteorological observatory Bratislava-Mlynska dolina were statistically analyzed. The data were analyzed based on Weibull and Rayleigh distribution. The distribution parameters were estimated using maximum likelihood method. The both distributions were compared for their performance using the coefficient of determination and the root mean square error. The results indicate that the better performance can be obtained by the Weibull distribution.